The Success Factors: A Study of Amway in Malaysia - Loo, Weng Tuck; Kee, Daisy Mui Hung; Har, Chen Wei; Loo, Chee Leong; Hau, Wai Meng; Sara, Alotaibi; Ekta, Bajpai (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The paper presents the success factor of Amway in Malaysia. The paper proposes that leadership, teamwork and continuous improvement are the key success factors of Amway in Malaysia. Amway Malaysia is a multi-level marketing company that established in 1976. Amway employees are always motivated by their leaders and they focus on results. The study employs a qualitative methodology with face to face interviews. The paper concludes with some recommendation.